The Use of Social Media Amid Government, Mass Media, and Non Government Organisations Responsibilities Due to Haze Disaster (Faculty of Communications Science, Dr. Soetomo University, 2017)
The haze disaster that have been devastating many regions in Indonesia from July to October 2015, was stated as national tragedy by the Government. As a consequence, there were many cases of public health deterioration.There were many efforts done to tackle this crisis due to provision of public information. In a contrary, there were also many angry public statements and dissatisfaction. This paper will scrutinize the content of using social media, particularly twitter, as various channels and mediums employed in order to cast overwhelming information to public. This is because social media pervasively and easily gets through to wide range of public. It has a high promptness and simplicity in stating effective messaging. The observation conducted through collecting data during the haze have been occuring since July until October 2015. Furthermore, the research will pore over public communication that commited by the National Disaster and Mitigation Guard, Non Government Organization and Mass Media. More over, the research is part of risk and crisis communication in overcoming the mitigation of haze disaster and due to public health. The outcome will be able to contribute to figure out the tendency of risk and crisis communication patterns in Indonesia. Finally, the conclusion leads to the relevancy of connectivity amid society, state and capitalists in public communication. Keywords: risk and crisis communication, haze disaster, social media.